The Preparations For The Coronation Of James II. And His Queen, In 1685 . (From Sandford's History, Published 1687.) (Tufts Archival Research Center, 2005)
This illustration is from Walter Thornbury "Old and new London, a narrative of its history, its people, and its places, vol. 3"